Konsep Maqashid Syariah Menurut Al-Syatibi Dan Kontribusinya Dalam Kebijakan Fiskal - Nabila Zatadini; Syamsuri Syamsuri (AL-FALAH : Journal of Islamic Economics, 2018)
Economic inequality is a common problem for all people in the world. To overcome this inequality government intervention is needed through fiscal policy. Successful fiscal policy took place during the Caliphate Umar bin Abdul Aziz who used maqashid sharia as its foundation. One Muslim scholar who has deep thoughts about maqashid sharia and contributes to the economy is Imam al-Syatibi. For this reason, research is needed on Maqashid Shari'ah and its contribution to fiscal policy. This paper aims to examine al-Syatibi's thought about maqashid syari'ah followed by its contribution to fiscal policy. The results of this study are maqashid sharia according to al-Syatibi aimed at maslahah which is classified into three dimensions: primary, secondary, and complementary. Maqashid Shari'ah has a big contribution in three aspects of fiscal policy, namely state expenditure, tax collection and household costs.